Blastocystis subtype 1 (allele 4); Predominant subtype among tuberculosis patients in Iran. (August 2019) - Taghipour, Ali; Javanmard, Ehsan; Mirjalali, Hamed; Haghighi, Ali; Tabarsi, Payam; Sohrabi, Mohamad Reza; Zali, Mohammad Reza
Highlights: Tuberculosis (TB) is one of the most important life-threating public health issues in the world. Blastocystis is a prevalent intestinal parasite in humans and animals. Distribution of Blastocystis subtypes and alleles were investigated among TB patients. Subtype 1 allele 4 was predominant among TB patients. Abstract: Background: Blastocystis and tuberculosis are two public health issues that are frequently reported in regions with low level of hygiene. Therefore, the current study aimed to investigate Blastocystis subtype and allele distribution in TB patients. Methods: Totally, 161 stool samples were taken from TB patients who were undergoing anti-MTB treatment. Stool samples were concentrated using conventional formalin-ether technique and examined using Lugol's iodine staining under light microscopy. DNA extraction was carried out and discriminative fragment was amplified and sequenced. With comparison in GenBank database, relevant subtypes and alleles were characterized and phylogenetically analyzed using MEGA v.7 and Tamura 3-parameter model. Results: In total, from 161 stool samples, 19 samples were suspected to be Blastocystis -positive. The expected fragment was amplified in 13 (8.07%) of samples. Accordingly, 11/13 (84.62%) of Blastocystis cases settled in urban and 2/13 (15.38%) were villagers. Close-contact with animals was also seen among 7/13 (53.84%) of samples. Subtype 1 (7/13; 53.84%) was the most prevalent followed by subtype 2 (5/13; 38.46%) and subtype 3 (1/13, 7.69%). All ST1 were allele 4, while alleles 9, 11 and 12 were seen in ST2 and allele 34 was the only allele observed in ST3. All three subtypes were clearly separated, while there was no separation between sequences from TB and non-TB patients. Conclusion: Blastocystis ST1 was the most prevalent subtype in TB patients and there was no difference between Blastocystis isolates from TB and non-TB human subjects.